Eksplorasi Pemahaman Mahasiswa Pendidikan Fisika Tentang Artikel Ilmiah Melalui Pelatihan Penulisan Akademik - Sirait, Jeliana Veronika; Erlida Amnie; Putri, Aprilia Kartika; Amri, Ulil (Pendidikan Sejarah FKIP Universitas JAMBI, 2026)
Understanding scientific articles is a fundamental competency that students must master from the beginning of their studies, but first-semester Physics Education students generally do not have an adequate understanding of the structure, conventions, and types of scientific texts. This gap has the potential to hinder their ability to access, analyze, and produce scientific knowledge, which is a primary demand in higher education. This community service activity aims to explore students' initial understanding of scientific articles and improve it through genre-based academic writing training conducted offline. The activity was carried out in three stages: the preparation stage which includes a needs analysis; the implementation stage which includes an introduction to scientific articles, IMRaD structure, abstract writing, APA 7 citation conventions, writing ethics, and integrative exercises; and the evaluation stage through a questionnaire. Participants were 23 first-semester Physics Education Study Program students, Class of 2025. Data were collected using an initial perception questionnaire and a final perception questionnaire with a five-point Likert scale, then analyzed using descriptive statistics and a normalized N-Gain test. The results showed an increase in the average score per item from 3.90 to 4.38, with an N-Gain of 0.44, which is considered moderate. After the training, all participants responded positively (100%). This activity proved effective in building students' conceptual understanding, self-confidence, and academic motivation for writing scientific articles.